Myanmar : Technical Assistance Report-External Sector Statistics Mission. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2020)
This Technical Assistance (TA) report on Myanmar presents outcomes and priority recommendations of mission on external sector statistics (ESS) for the Directorate of Investment and Company Administration (DICA). Intensive hands-on training provided to the DICA through peripatetic TA missions have effectively contributed to building up capacity for DICA compilers, which have gradually materialized and translated into successful foreign direct investment surveys (FDIS) conducted last year. Data coverage has significantly improved through inclusion of FDI in oil and gas sector, which is one of the largest FDI recipients for Myanmar. In order to further enhance the coverage of Myanmar's FDI statistics, the mission advised the DICA to extend the coverage of FDIS to incorporate new companies and FDI in power generation sector. The mission also assisted DICA officials in updating the annual FDIS survey forms, making alterations to the previous year's survey forms to capture additional information as requested by DICA management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Company; CR; FDI Company; ISCR; Sampling Frame; Myanmar